Effect of hypertrophic cardiomyopathy mutations in human cardiac muscle alpha -tropomyosin (Asp175Asn and Glu180Gly) on the regulatory properties of human cardiac troponin determined by in vitro motility assay. - Bing, W; Knott, A; Redwood, C; Esposito, G; Purcell, I; Watkins, H; Marston, S (2000)
The properties of mutant contractile proteins that cause hypertrophic cardiomyopathy (HCM) have been investigated in expression studies and in mouse models. There is growing evidence that the precise isoforms of both the mutated protein and its interacting partners can qualitatively influence the effects of the mutation. We therefore investigated the functional effects of two HCM mutations in alpha -tropomyosin, Asp175Asn and Glu180Gly, in the in vitro motility assay using recombinant human alpha -tropomyosin, expressed with an N-terminal alanine-serine extension (AStm) to mimic acetylation in vivo, and purified native human cardiac troponin. The expected switching off of reconstituted filament movement at pCa9, and switching on at pCa5, was observed with no difference in fraction of filaments motile or filament velocity, between wild-type and mutant filaments. However, we observed increased Ca(2+)sensitivity of fraction of filaments motile using the mutant tropomyosin compared to wild-type (DeltaEC(50)+0.082+/-0. 019 pCa units for Asp175Asn and +0.115+/-0.021 for Glu180Gly). Indirect measurements using immobilized alpha -actinin to retard filament movement showed that filaments reconstituted with mutant AStm produced the same force as wild-type filaments. The results using human cardiac regulatory proteins reveal different effects of the HCM mutations in tropomyosin compared to studies using heterologous systems. By performing parallel experiments using either human cardiac or rabbit skeletal troponin we show that the cardiac-specific phenotype of HCM mutations in alpha -tropomyosin is not the result of more marked functional changes when interacting with cardiac troponin.